2022
DOI: 10.1111/bcp.15186
|View full text |Cite
|
Sign up to set email alerts
|

Association of weekly or biweekly use of 50 000 IU vitamin D3 with hypervitaminosis D

Abstract: Since the beginning of the COVID‐19 pandemic, many Iranian people have been taking 50 000 IU of vitamin D3 on weekly or biweekly bases in order to enhance their immune system function. This cross‐sectional study was conducted on the patients of endocrinology clinic to compare 25(OH)D levels of weekly or biweekly consumption with the monthly users of vitamin D3 50 000 IU. The level >100 ng/mL of 25(OH)D was defined as hypervitaminosis D. In total, 211 patients (108 and 103 patients in monthly and weekly/biweekl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In a study, the rates of hypervitaminosis were reported as 18.9% and 4.5% in weekly and biweekly users of 50,000 IU of Vit. D 3, respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study, the rates of hypervitaminosis were reported as 18.9% and 4.5% in weekly and biweekly users of 50,000 IU of Vit. D 3, respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research on vitamin C and vitamin D status remains ongoing on the grounds that their deficiency may be associated with increased susceptibility to COVID-19 infection and to potentially more severe or prolonged symptoms once infected [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Because medical prescription is not needed for their procurement, misinformed assurances with silent contraindications about vitamin supplements could lead to harmful intakes, unsafe combinations, and misuse by the public, as seen in hypervitaminosis and intoxication case reports during the global pandemic [ 36 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to elucidate this issue for two reasons, first to avoid requests for tests of serum 25(OH)D in patients indiscriminately [59]; and secondly, to prevent vitamin D toxicity reactions from overtreatment [60][61][62]. Even though vitamin D toxicity is not likely when oral supplements are taken below 2000 international units/day, before the COVID-19 pandemic, acute kidney injury due to overcorrection of hypovitaminosis D has been reported [63,64].…”
Section: Why Is It Important To Determine the Nature Of The Associati...mentioning
confidence: 99%